2016
DOI: 10.1016/j.pce.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Spatial scale impact on daily surface water and sediment fluxes in Thukela river, South Africa

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…6), plot-scale runoff response generally exceeded watershed-scale discharge response. In agreement with this, Mutema et al (2015), a study in South Africa, observed a significant reduction in unit runoff as plot size increased from micro-plots (1 m 2 ) to plots (10 m 2 ) and subsequently to mico-catchments (0.23 km 2 ). Similarly, van de Giesen et al (2011) reported that runoff decreased with increases in plot size.…”
Section: Plot Runoff and Outlet Dischargesupporting
confidence: 66%
“…6), plot-scale runoff response generally exceeded watershed-scale discharge response. In agreement with this, Mutema et al (2015), a study in South Africa, observed a significant reduction in unit runoff as plot size increased from micro-plots (1 m 2 ) to plots (10 m 2 ) and subsequently to mico-catchments (0.23 km 2 ). Similarly, van de Giesen et al (2011) reported that runoff decreased with increases in plot size.…”
Section: Plot Runoff and Outlet Dischargesupporting
confidence: 66%
“…Table ; Figure ). These findings are concordant with studies where slope gradient was identified as the main driver of runoff generation at a global scale (Chaplot et al, ; Mutema et al, ; Mhazo et al, ; Prosdocimi et al, ). Notably, measured soil organic matter (i.e., SOC and N content and stocks) correlated positively to unit‐area runoff, but negatively to soil losses, implying greater runoff with low detachment and sediment transportation.…”
Section: Discussionsupporting
confidence: 90%
“…The changes of average q (in l m ‐2 day ‐1 ) and SL (in g m ‐2 day ‐1 ) fluxes with contributing area were described in greater detail by Mutema et al . (). The q decreased by 24% between microplot and plot scale, followed by a steeper 76% decrease from plot to microcatchment scale (Table ) and further decrease in a downstream direction, by 4.3 fold from microcatchment to subcatchment, and by over 99% from subcatchment to catchment level.…”
Section: Resultsmentioning
confidence: 97%
“…Negative correlations at microcatchment scale could be indicative of increased C‐rich baseflow into streamflow. Past studies reported high baseflow contribution to streamflow at this outlet (Chaplot and Ribolzi, ; Mutema et al ., ). Once the dissolved C joins the open streamflow system, it mineralizes rapidly but the relatively stable particulate C remains in transit and that explains positive correlations at subcatchment and other downstream outlets.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation